Cutaneous habronemosis in horses: First molecular characterization of Habronema muscae in Israel. (April 2021) - Salant, H.; Rojas, A.; Yardeny, D.; Brenner, O.; Schvartz, G.; Baneth, G.; Dvir, E.
Highlights: The first case series of equine cutaneous habronemiasis in Israel is reported. Five cases were confirmed by molecular or histopathological methods. Habronemiasis by Habronema muscae was confirmed molecularly for the first time in Israel. Abstract: Draschia megastoma, Habronema microstoma, and Habronema muscae are the etiological agents of cutaneous habronemosis, commonly known as summer sores, an inflammatory cutaneous and ocular parasitic disease of horses and other equids transmitted by flies. Here, we describe a cluster of cutaneous habronemosis in five horses that showed single or multiple typical cutaneous ulcerative wounds located on the face, lower forelegs or hindquarters in Israel with the presence of typical "sulphur granules." All affected animals were confirmed by histopathological and/or molecular methods to be infected by H. muscae . This constitutes the first report of cutaneous habronemosis in Israel in which the causative nematode, H. muscae, was identified by molecular means. Cutaneous habronemosis should be considered as a differential diagnosis in equids with cutaneous ulcerative lesions during the summer months, especially when affected animals are refractive to antibiotic treatment alone.